Job Satisfaction, Job Stress, Organizational Commitmet and Intention to leave among the Employees of Sarawak Energy Berhad (SEB). / Mohamad Iskanda Mohamad Muar... [et al.] - Mohamad Muar, Mohamad Iskanda; Salihin, Zunnasri; Felix Bujek, Betty (2013)
The purpose of this study is to assess the level of job satisfaction, job stress, organizational commitment and intention to leave among employees of Sarawak Energy Bhd (SEB). The components of organizational commitment include affective commitment, continuance commitment and normative commitment. Sample populations are the staffs of SEB consist of executive and non-executive employees from various ages, working tenure and level of education.